Penilaian Penerapan Good Manufacturing Practices (GMP) pada Proses Produksi Dimsum (Studi Kasus : UMKM XYZ) - Arpi, Normalina; Eliza, Tasya; Aisyah, Yuliani (Jurnal Teknologi dan Industri Pertanian Indonesia, 2024)
Dimsum is a high-risk food category because it uses basic ingredients of chicken meat and these ingredients have a water content of around 65-80% and a high pH of around 6-7, as well as easily degraded and easy to grow microorganisms. This study aims to assess the application of GMP in the production process in Aceh Dimsum Micro, Small and Medium Enterprises (UMKM) and the application of GMP is the basic requirement for granting a distribution permit certificate for the Deep Food (MD) category by the Food and Drug Supervisory Agency (BPOM). In this study, the assessment of the application of GMP in dimsum production process was carried out using the Gap Assessment method by assessing the suitability and non-conformity of the GMP aspects applied. The assessment is carried out by giving value weight to the finding of nonconformity based on the category of nonconformity. From the results of the research that has been carried out, conformity findings, nonconformity findings, and GMP aspect findings that are not applied to the production process are obtained. There are 17 points of conformity findings applied from 12 aspects of GMP. There were 51 points of nonconformity findings found from 21 aspects of GMP. There are 2 points of aspects that do not apply or are not used to UMKM from 2 aspects of GMP (aspects of internal testing laboratories and aspects of water, ice, gas and energy (electricity, fuel). Based on the amount of value weighted obtained from the findings of nonconformity, the score obtained by UMKM is around a score of 78. Based on this score, the level (rating) of UMKM is rating D. The conclusion that can be drawn is that UMKM need to make improvements to the discrepancies found in the production process.